Woman’s Da’wah Communication Strategies for Generation Z: A Study of Viral Cultural Phenomena on Social Media - Hardianti, Riski; Rahmawati, Endang; Suhadah, Suhadah (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2026)
The development of digital communication technology has brought significant changes to contemporary da'wah practices, particularly through the use of social media, which has become the main space for interaction for Generation Z. This condition opens up wider opportunities for young female preachers to convey Islamic messages through various digital platforms. However, the rise of viral culture on social media also presents challenges in maintaining the authenticity of religious messages while adapting them to the ever-evolving dynamics of digital culture. Therefore, this study aims to analyze the communication strategies used by Generation Z female preachers in responding to viral culture on social media without compromising the authenticity of Islamic preaching messages. This study uses a descriptive qualitative approach with content analysis methods on seven preaching contents published by Dinda Ibrahim through the Instagram platform. Data were collected through documentation techniques on digital content and analyzed using the Miles and Huberman data analysis model, which includes the stages of data collection, data reduction, data presentation, and conclusion drawing. The results of the study show three main strategies for digital da'wah, namely the internalization of moral values through contextual narratives and dialogic communication, the development of digital authenticity and credibility through consistency of values and emotional closeness with the audience, and the use of visual aesthetics as a language of da'wah through the use of humor, cosplay, and curated visual packaging. These findings indicate that the integration of moral narratives, authentic communication, and visual aesthetics keeps digital da'wah relevant and effective for Generation Z audiences.